Medulloblastoma with Subcutaneous Spread: A Rare Entity - Srinivasan, Siddharth; Hegde, Ajay; Nair, Rajesh; Menon, Girish (Asian Journal of Neurosurgery, 2023)
Medulloblastoma is the most common malignant pediatric brain tumor. Histological subclassification and adjuvant therapy have improved prognostication and outcome. Extraneural metastasis remains a poor prognostic factor and subcutaneous seeding is rarely encountered and reported in the pediatric population. We report a 3-year-old child who rapidly presented with subcutaneous seeding a month following gross total resection of his tumor.
Keywords: extraneural metastasis; medulloblastoma; pediatric; subcutaneous spread